Determination of the Proteomic Response to Lapatinib Treatment using a Comprehensive and Reproducible Ion-Current-Based Proteomics Strategy - O’Connell Kathleen; Li Jun; Engler Frank; Hennessy Kim; O’Neill Fiona; M Straubinger Robert; Qu Jun; O’Connor Robert (Journal of Proteomics and Genomics Research, 2013)
Lapatinib, a small molecule tyrosine kinase inhibitor is currently used in the treatment of HER2-positive breast cancer. The aim of this study was to further understanding of lapatinib response for the development of novel treatment lapatinib-focussed treatment strategies. HER2-overexpressing SKBR3 breast cancer cells were treated with lapatinib for 12 hours and the resultant proteome analyzed by a comprehensive ion-current-based LC-MS strategy. Among the 1224 unique protein identified from SKBR3 cell lysates, 67 showed a significant change in protein abundance in response to lapatinib. Of these, CENPE a centromeric protein with increased abundance, was chosen for further validation. Knockdown and inhibition of CENPE demonstrated that CENPE enhances SKBR3 cell survival in the presence of lapatinib. Based on this study, CENPE inhibitors may warrant further investigation for use in combination with lapatinib.
Keywords: Breast